OPTIMALISASI BAHAN AJAR PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA - Waris, Abdul (LPPM IAIN Parepare, 2018)
This article discusses the relationship between the usage of IT-based teaching materials on Islamic education and learning interests with learning outcomes of Student in SMPN 1 Cempa Pinrang. This research was a field research. Refereeing from the type of data, this study included quantitative research. The approach used was the pedagogical approaches. Data were obtained through a questionnaire that had been tested for validity and reliability, then the data were analyzed using descriptive and inferential method. These results indicated that; perception of students on the use of IT-based teaching materials of PAI was in medium category, while PAI learning interest of students was in the high category. This study showed that the use of IT-based teaching materials of PAI and interests simultaneously can give a positive contribution to the learning outcomes of PAI. The implication of this research is that the use of IT-based teaching materials of PAI will provide a significant contribution in the implementation of the learning process for teachers because of the use of IT-based teaching materials of PAI provides convenience in learning so the impact on the effectiveness of the learning process that can further enhance the learning outcomes of students.